Ventricular Pneumocephalus with Meningitis after Lumbar Nerve Root Block. (16th May 2013) - Ahn, Shin; Ko, Young Sang; Lim, Kyung Soo
Abstract : Lumbar nerve root block is a common modality used in the management of radiculopathy. Its complications are rare and usually minor. Despite its low morbidity, significant acute events can occur. Pneumocephalus is an accumulation of air in the intracranial space. It indicates a violation of the dura or the presence of infection. The object of this report is to describe the case of a patient with intraventricular pneumocephalus and bacterial meningitis after lumbar nerve root block. A 70-year-old female was brought into emergency department with severe headache and vomiting which developed during her sleep. She had received lumbar nerve block for her radiculopathy one day before her presentation. Cranial computed tomography scan revealed a few hypodense lesions in her left lateral ventricle frontal horn and basal cistern indicating ventricular pneumocephalus. Five hours later, she developed sudden hearing loss. Cerebrospinal fluid analysis showed bacterial meningitis, and she was treated with high dose steroid and antibiotics. However, her impaired hearing as a sequela from meningitis was persistent, and she is still in follow-up. Intracranial complications of lumbar nerve root block including meningitis and pneumocephalus can occur and should be considered as high-risk conditions that require prompt intervention.